Implementation of learning video on mathematical analogic thinking ability in solving pythagoras theorem problems - Rahma Damayanti, Laily Nur (International Journal on Teaching and Learning Mathematics, 2023)
The problem in this study is related to the low ability to think mathematically analogies of junior high school students which can be seen when students work on the board they are still confused about which formula to use, and if they can determine which formula to use the numbers or questions that are included in the formula are not appropriate. Because teachers tend to be preoccupied with how to ensure that all material can be delivered based on the time allocation available. This makes students understand a little mathematical concepts, whether it's related to the formula used, how to do it, and even some children tend to not understand what material is conveyed by the teacher. One solution to this problem is the use of video-based learning media that students can access at any time. This research is a qualitative research. The results of this study were students with low ability to think mathematically analogies (A1) were unable from the start, at the encoding, inferring, mapping and applying stages. Students with moderate mathematical analogy thinking skills (A2) were able to pass the encoding and inferring stages but failed at the mapping and applying stages. Students with high mathematical analogy thinking skills (A3) were able to pass the encoding, inferring, and mapping stages but failed at the applying stage. This proves that there are still students who are less able to think mathematical analogies even though they have been assisted by the use of learning video media.